Skin-to-skin SDF positioning: The key to intersubjective intimacy between mother and very preterm newborn—A pilot matched-pair case-control study - Buil, Aude; Sankey, Carol; Caeymaex, Laurence; Gratier, Maya; Apter, Gisèle; Vitte, Lisa; Devouche, Emmanuel (Frontiers in Psychology, 2022)
Background Skin-to-skin contact (SSC) has been widely studied in NICU and several meta-analyses have looked at its benefits, for both the baby and the parent. However, very few studies have investigated SSC’ benefits for communication, in particular in the very-preterm newborn immediately after birth. Aims To investigate the immediate benefits of Supported Diagonal Flexion (SDF) positioning during SSC on the quality of mother—very-preterm newborn communication and to examine the coordination of the timing of communicative behaviors, just a few days after birth. Subjects and study design Monocentric prospective matched-pair case-control study. Thirty-four mothers and their very preterm infants (27 to 31 + 6 weeks GA, mean age at birth: 30 weeks GA) were assigned to one of the two SSC positioning, either the Vertical Control positioning (n = 17) or the SDF Intervention positioning (n = 17). Mother and newborn were filmed during the first 5 min of their first SSC. Outcome measures Infants’ states of consciousness according to the Assessment of Preterm Infants’ Behavior scale (APIB). Onset and duration of newborns’ and mothers’ vocalizations and their temporal proximity within a 1-s time-window. Results In comparison with the Vertical group, very preterm newborns in the SDF Intervention Group spent less time in a drowsy state and more in deep sleep. At 3.5 days of life, newborns’ vocal production in SSC did not differ significantly between the two groups. Mothers offered a denser vocal envelope in the SDF group than in the Vertical group and their vocalizations were on average significantly longer. Moreover, in a one-second time-frame, temporal proximity of mother-very preterm newborn behaviors was greater in the SDF Intervention Group. Conclusion Although conducted on a limited number of dyads, our study shows that SDF positioning fosters mother-very preterm newborn intimate encounter during the very first skin to skin contact after delivery. Our pioneer data sheds light on the way a mother and her very preterm vocally meet, and constitutes a pilot step in the exploration of innate intersubjectivity in the context of very preterm birth.